تأثير ازمة الكورونا على ميزان المدفوعات الجزائري - البشير, احمادي; هزله, سمير (University of eloued جامعة الوادي, 2021)
"تهدف هذه الدراسة الى دراسة وضعية واثر ميزان المدفوعات الجزائري في ظل جائحة كورونا كوفيد – 19 خلال 2019 و2020، وقد سعت الدراسة الى معرفة السياسات الاقتصادية التي انتهجتها الدولة الجزائرية مع الازمة الاقتصادية. لمعالجة هذه البحث إعتمدنا على المنهج الوصفي لتوضيح الإطار النظري لكل من ميزان المدفوعات وفايروس كورونا وما يتضمنها، أما الجانب التطبيقي استخدامنا المنهج التحليلي لتحليل المؤشرات المستخرجة من المواقع الرسمية لتغطية جوانب الموضوع بما يتلائم مع طبيعة المشكلة. وقد توصلنا الى ان الازمة الصحية تبعتها ازمة اقتصادية وتأثير سلبي لميزان المدفوعات تمثل في عجز الميزان بنسبة 57%. ""This study aims to examine the status and impact of the Algerian balance of payments under the corona virus (COVID-19) pandemic during 2019 and 2020, and sought to identify the economic policies adopted by the Algerian state in response to the economic crisis. To address this research, we have relied on the descriptive method to clarify the theoretical framework of the balance of payments and the corona virus and its implications. As for the practical aspect, we use the analytical method to analyze the indicators extracted from official websites to cover the aspects of the issue in line with the nature of the problem. We have concluded that the health crisis was followed by an economic crisis and a negative balance of payments effect of a 57% deficit. "
مذكرة ماستر مالية وتجارة دولية
Keywords: فيروس كورونا، كوفيد – 19، ميزان المدفوعات، القطاع الاقتصادي.; COVID-19, balance of payments, economic sector.